Financial ratios and stock prices in Indonesian retail firms: A panel data analysis - Supriyatto Surbakti; Kristian Pratama; Hendriko Iswahyudi (Jurnalku, 2026)
The volatility of Indonesian retail sector stock prices during the pandemic raises questions regarding the resilience of fundamental indicators in explaining price movements. This study examines the influence of Return on Assets (ROA), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on the stock prices of 16 retail companies listed on the Indonesia Stock Exchange during the 2018–2022 period. The analytical technique employed in this study is panel data regression using EViews 12 software. The results indicate that ROA has a significant positive influence on stock price, whereas DER and TATO do not exert significant partial effects. Simultaneously, the three financial ratios collectively demonstrate a significant influence on stock price with an explanatory power of 11.4%. These findings suggest that amid market uncertainty, Indonesian retail investors continue to respond to profitability as the primary signal, while capital structure and operational efficiency play a limited role in determining stock prices within this sector.